Microwave Electronics - Grigoriev, Andrey D.; Ivanov, Vyacheslav A.; Molokovsky, Sergey I.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book describes the physical basis of microwave electronics and related topics, such as microwave vacuum and microwave semiconductor devices. It comprehensively discusses the main types of microwave vacuum and microwave semiconductor devices, their principles of action, theory, parameters and characteristics, as well as ways of increasing the frequency limit of various devices up to the terahertz frequency band. Further, it applies a unified approach to describe charged particle interaction within electromagnetic fields and the motion laws of charged particles in various media.  The book is intended as a manual for researchers and engineers, as well as advanced undergraduate and graduate students.
Preface -- Part 1. Physical bases of microwave electronics -- History of microwave electronics -- Basic laws of microwave electronics -- Oscillations and waves in charged particles beams -- Charged particle interaction with alternating electromagnetic field -- Microwave device as an element of a microwave circuit -- Part 2. Vacuum electron devices -- Power grid tubes -- O-type microwave devices -- M-type microwave devices -- Gyro-resonance devices -- Relativistic devices -- Part 3. Solid-state microwave devices -- Main functional elements of solid state devices -- Diodes with positive dynamic impedance -- Diodes with negative dynamic impedance -- Microwave transistors.
Keywords: Telecommunication; Electronic circuits; Semiconductors; Microwaves, RF Engineering and Optical Communications; Electronic Circuits and Systems; Semiconductors